2009
DOI: 10.1158/1078-0432.ccr-09-1861
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Synergistic Combination of Cyclophosphamide and Gene Transfer of Interleukin-12 Eradicates Colorectal Carcinoma in Mice

Abstract: Purpose: Interleukin-12 (IL-12) is an immunostimulatory cytokine with potent antitumor effects in several animal models. However, serious toxicity has been associated with its systemic application in humans. Gene transfer has emerged as a tool to specifically express therapeutic genes into the tumor/peritumoral milieu, thus avoiding systemic toxicity. The aim of this study was to analyze whether subtherapeutic doses of an adenovirus encoding IL-12 (AdIL-12) might synergize with low immunopotentiating doses of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
35
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(37 citation statements)
references
References 42 publications
2
35
0
Order By: Relevance
“…Multiple immunotherapy strategies for colorectal carcinoma are currently under preclinical and clinical evaluation (21). Immunotherapy usually has to face strong mechanisms of immune escape induced by tumors.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Multiple immunotherapy strategies for colorectal carcinoma are currently under preclinical and clinical evaluation (21). Immunotherapy usually has to face strong mechanisms of immune escape induced by tumors.…”
Section: Discussionmentioning
confidence: 99%
“…To increase the efficacy of immunotherapy strategies, it is potentially interesting to explore therapeutic interventions that exploit tolerogenic processes such as those induced by T regs in tumor-bearing hosts (22). In this context, it has been shown that low-dose CYP decreases the number of T regs (8,21) and can enhance the antitumor activity of adoptively transferred T cells, as well as tumor vaccines (23). However, CYP may exert a toxic effect on other lymphocyte populations that could attenuate its immunostimulatory effect.…”
Section: Discussionmentioning
confidence: 99%
“…[77][78][79][80][81][82][83] Furthermore, the combination with chemotherapeutic or antiangiogenic agents in lung, skin and colorectal cancer, or with antiangiogenic agents in prostate cancer proved to be more efficient than viral-mediated IL-12 gene therapy alone in different types of tumors. [84][85][86][87][88][89] Even though local delivery of IL-12 by gene therapy resulted in a more sustained expression of IL-12 in comparison with the levels obtained by injecting the recombinant protein, the lack of selectivity and the occurrence of non-specific immune responses associated with the use of viral vectors remain a major concern when using this strategy to deliver IL-12.…”
Section: Therapeutic Effects Of Il-12 In Preclinical Modelsmentioning
confidence: 99%
“…In this direction, Malvicini et al 72 observed in a murine model of colorectal carcinoma that the combination of CTX with an IL-12-encoding adenovirus vector induces complete regression in more than 50% of tumor-bearing mice. Such treatment was able to decrease the number of peripheral and spleen Treg, at the same time that it increased the numbers of activated DC and IFN-c-secreting CD4þ lymphocytes.…”
Section: Effects Of Ctx On the Immune Response And Combination With Imentioning
confidence: 99%